A Survey an Egg of Helminthes in Fishing Cat (Prionailurus viverrinus) from Chiang Mai Night Safari - Vorawattanatham, Narathip; Kanungpean, Doungjit; Kanatiyanont, Nathavut; Suwantada, Pongthorn; Wattanachai, Suchat; Sringam, Sarawut; Pinyopummin, Anuchai (Journal of Mahanakorn Veterinary Medicine, 2018)
Fecal samples of 14 fishing cats from Chiang Mai Night Safari were examined by simple floatation and simple sedimentation methods. These results show 42.85% was found for fluke egg and 7.14% for roundworm egg. The cause of infection in fishing cat is being unknown. Therefore, this data can be utilized for control and prevention of internal parasite infestation with fishing cats. Furthermore, these data can be utilized for management, for example: sanitation and water drainage to reduce the contamination in natural water and outbreak to the other animals.